Trend Analysis of Sea Level Change in the Gulf of Thailand - Taninpong, Phimphaka; Minsan, Watha; Thumrongnavasawat, Salinee; Luangdang, Kanyarat (Science Essence Journal, 2021)
This study aims to examine the trend of sea level change in the Gulf of Thailand. This study uses sea level data of the 18 tide gauge stations during January 1977 until August 2019 from Marine Department, the Ministry of Transport in Thailand. Time series analysis is employed including seasonal removal and trend detection. Trend detection is checked by using both parametric and non-parametric statistics test. Autoregressive model is used to ensure that errors are independent, therefore linear regression can be used to assess the linear trend. The results show that the rate of change in sea level varies from station to station and only 13 tide gauge stations show significant increasing in sea level. In addition, sea level change has linearly increased from 3.44 to 19.19 mm/year. The highest rate of sea level change appears in the eastern coast of the Gulf of Thailand since sea level change at Ao Udom, Chonburi province has linearly increasing of 19.19 mm/year.